Оцінка енергетичних характеристик вітрового потоку - Ramsh, V.; Potapenko, M.; Sharshon, V.; Darmoris , P. (Energy and Automation, 2025)
Wind is a renewable and environmentally friendly source of energy, unlike fossil fuels that pollute the lower atmosphere. Assessment of wind flow characteristics is essential to ensure the reliability and efficiency of wind power systems. Accurate determination of the statistical distribution of wind speed is very important in assessing the energy potential of a particular area. This information is necessary for developers of wind power installations, which allows minimizing the costs of their production. The purpose of the study is to analyze and evaluate the energy characteristics of wind potential. Wind potential modeling is necessary both for choosing a rational structure of a wind power plant and for building energy-efficient algorithms for controlling the operating modes of generating units of an autonomous power supply system. A model of wind speed changes based on the Weibull distribution allows you to select a wind power installation and qualitatively assess its energy characteristics. When choosing the type of wind power plant and calculating its annual energy production, one cannot proceed only from the average annual wind speed for a given area, but must take into account the data on the repeatability of different wind speeds, which are usually approximated by the Weibull distribution function. A method for determining the parameters of the Weibull function, which reflect the probability density distribution of wind flow speeds at a given base height above the surface, using available data on the average speed at this height and its repeatability by gradations, is presented. This is important for ensuring the stability and reliability of the power system, as it reduces the likelihood of power outages, thereby ensuring a more even distribution of the load. Thus, the assessment of wind flow characteristics is essential to ensure the reliability and efficiency of wind power systems. Key words: wind power installation, wind potential, wind speed, repeatability of wind speeds, distribution function, forecasting